PENGARUH PEMANFAATAN OPTIMAL FASILITAS BELAJAR DAN TINGKAT PENDIDIKAN ORANG TUA TERHADAP PRESTASI BELAJAR MATEMATIKA SISWA SEKOLAH DASAR - Alisya Amanda; Hikma Ramadhani; Andi Syamsinar; A.Muhajir Nasir; Siti Zahra Mulianti Natsir (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The problem in this study relates to the variation in students’ mathematics achievement influenced by differences in learning facility use and parental education levels. Some parents have limited time to accompany their children in studying, while available learning facilities are not always used optimally. This study aims to describe the use of learning facilities, parental education levels, and their influence on students’ mathematics achievement at SDIT Azzahrah. This research employed a quantitative expost facto design with a sample of 30 students. Data were collected through questionnaires, parental education records, and mathematics report cards. Descriptive statistics and multiple linear regression were used for data analysis. The results showed that learning facility utilization was in the moderate category, parental education levels were medium to high, and mathematics achievement was in the fairly good category. However, inferential analysis revealed that both variables did not significantly influence mathematics achievement, either partially or simultaneously.